(untitled) (Revista de Ciências Agroveterinárias, 2018)
The use of permanent or partial vegetative cover of the soil in the vineyards can influence the production and the quality of the grape. Thus, the objective of this work was to evaluate the development of the grapevine productivity as well as the qualitative characteristics of ‘Isabel’ grape, in consortium with soil cover plants. The experiment was conducted in the municipality of Itapuranga, GO, and consisted of six treatments established in a randomized block design, in a 3 x 2 factorial scheme, in five replications. The first factor consisted of a plant species cover the soil: Jack Beans (Canavalia ensiformis L. DC), lab-lab (Dolichos lab lab L.) and spontaneous plants. In the second factor, there were two pruning seasons of the grapevine crop, based on the sowing of the cover crops. In other words, the first pruning season in the vine was performed 25 days after sowing (DAS) of the cover plants and the second pruning season in the vine was performed at 55 DAS. In three crop cycles, the soil cover plants consortium with the grapevine does not influence the morphological variables, the productivity, the variables associated with the productivity and the qualitative characteristics of the grape. Different times of pruning influence the productivity and the associated variables in the grape crop. The pruning at 25 days after sowing of the cover plants presented better results for the morphological variables and qualitative characteristics of the grape. Therefore, for the local conditions and for the evaluated time, use of hedge plants did not influence the production of the vines as well as the quality of the grape. However pruning times can affect the development of the vine, reflecting its productivity and quality.